Pengaruh Penambahan Feri Klorida pada Media NPSi terhadap Biomassa dan Kandungan Protein Mikroalga Chaetoceros calcitrans - Ananta Wijaya Putra, I Gusti Bagus; Dewi Anggreni, Anak Agung Made; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret, 2017)
This study aims were to know the effect of ferric chloride (FeCl3) on biomass concentration and protein content of microalgae Chaetoceros calcitrans and determine the best concentration of ferric chloride for production of microalgae Chaetoceros calcitrans with highest protein content. This study was designed with randomized block design with single factor. The factor was different ferric chloride concentration consist of 4 concentration, i.e. 0 µM, 12 µM, 24 µM and 36 µM. Each treatment was grouped into 4 based on time of cultivation. The data obtained were analyzed by analyzed of variance followed by least significant difference test, if a treatment had significant effect. The result showed that addition of ferric chloride had very significant effect on the b iomass concentration and protein content. The highest biomass concentration and protein content was obtained from the microalgae Chaetoceros calcitrans which was cultivated in 36 µM ferric chloride amounted of 4.1 x 10 7 cell/mL and 25.41%. Keywords: biomass, Chaetoceros calcitrans, Ferric Chloride, NPSi, protein.
Keywords: 127